Pulsed Electric Field Induces Significant Changes in the Metabolome of Fusarium Species and Decreases Their Viability and Toxigenicity - Behner, Adam; Palicova, Jana; Tobolkova, Anna-Hirt; Prusova, Nela; Stranska, Milena (Toxins, 2025)
Fusarium fungi are widespread pathogens of food crops, primarily associated with the formation of mycotoxins. Therefore, effective mitigation strategies for these toxicogenic microorganisms are required. In this study, the potential of pulsed electric field (PEF) as an advanced technology of increasing use in the food processing industry was investigated to minimize the viability of Fusarium pathogens and to characterize the PEF-induced changes at the metabolomic level. Spores of four Fusarium species (Fusarium culmorum, Fusarium graminearum, Fusarium poae, and Fusarium sporotrichioides) were treated with PEF and cultured on potato dextrose agar (PDA) plates. The viability of the Fusarium species was assessed by counting the colony-forming units, and changes in the mycotoxin content and metabolomic fingerprints were evaluated by using UHPLC-HRMS/MS instrumental analysis. For metabolomic data processing and compound identification, the MS-DIAL (v. 4.80)-MS-CleanR-MS-Finder (v. 3.52) software platform was used. As we found out, both fungal viability and the ability to produce mycotoxins significantly decreased after the PEF treatment for all of the species tested. The metabolomes of the treated and untreated fungi showed statistically significant differences, and PEF-associated biomarkers from the classes oxidized fatty acid derivatives, cyclic hexapeptides, macrolides, pyranocoumarins, carbazoles, and guanidines were identified.
Keywords: mycotoxins; Mycotoxins; Metabolomics; UHPLC-HRMS/MS; mikrobiální viabilita; metabolomika; biomarkers; metabolomic fingerprinting; food pathogens; elektřina; spore viability; Spores, Fungal; spory hub; Microbial Viability; Electricity; Fusarium; pulsed electric field; Metabolome; metabolom; mykotoxiny